Body mass index and physical fitness among Chinese adolescents from Shandong Province: a cross-sectional study - Xiangren Yi; You Fu; Ryan D. Burns; Yang Bai; Peng Zhang (BMC, 2019)
Abstract Background This study aimed to describe the most recent prevalence estimates of adolescent body mass index (BMI) and physical fitness from thirteen regions in Shandong Province, China and to examine differences by social-economic status (SES). Methods The participants were 27,955 adolescents (mean age = 14.4 ± 1.8 years; 13,791 girls) enrolled from 91 public middle and high schools randomly selected from 13 administrative regions in Shandong Province. The Chinese National Student Physical Fitness Standard was employed to assess participants' fitness once during the school semester. Fitness assessments included BMI, a 50-m sprint run, sit-and-reach, standing-broad jump, sit-ups, pull-ups, and a 1000 m/boy or 800 m/girl distance run. Participants' fitness performance was categorized as excellent, good, pass, or no pass. Results The percent of Chinese adolescents categorized as "no pass" ranged from just 8.9% for BMI to 67.1% for boy pull-ups. The percent of Chinese adolescents categorized as "excellent" ranged from 5.0% for the girl sit-ups to 35.4% for the 50-m sprint run. Approximately 8.4% of the sample was categorized as excellent for BMI. SES significantly predicted both girl and boy continuous distance run scores (p < 0.05). Adolescents in lower SES strata had lower odds of achieving "pass" or better on cardio-respiratory endurance tests, muscular fitness tests, and flexibility tests, but higher odds of achieving "pass" or better on BMI compared to adolescents who were high SES (p < 0.05). Conclusions The large sample of the adolescents in Shandong province, on average, had healthy weight status and achieved a high prevalence of "pass" or better on physical fitness tests. Adolescents who were low SES demonstrated poorer cardio-respiratory endurance, muscular fitness, and flexibility test achievement but better BMI achievement compared to high SES adolescents in Shandong Province, China.